APA MAKNA “KEUNTUNGAN” BAGI PROFESI DOKTER? - Dian Purnama Sari (Universitas Brawijaya, 2014)
Abstract: What is the meaning of “profit” for doctor profession? This research’s goal is to understand the meaning of “profit” which is seen from doctor’s side. With Intensionalism Hermeneutic as research method, this research concludes that there are four meanings of “profit” for doctor profession. The first meaning is material “profit” which is called as saving to fulfill doctor’s needs. The second meaning is spiritual “profit” addressed for fellow being and return to God. The third meaning is prestige “profit” which is respected enough in society. And the fourth meaning is satisfaction of mind “profit” when the patient is cured and healthy.Abstrak: Apa makna “keuntungan” bagi profesi dokter? Tujuan penelitian ini adalah untuk memahami makna “keuntungan” yang dilihat dari sudut pandang profesi dokter. Dengan menggunakan hermeneutika intensionalisme sebagai metode penelitian, penelitian ini menyimpulkan empat makna “keuntungan” bagi profesi dokter. Makna pertama adalah “keuntungan” materi yang disebut tabungan untuk memenuhi kebutuhan dokter. Makna kedua adalah “keuntungan” spiritual dalam selalu menolong orang lain maupun mengembalikannya kepada Tuhan. Makna ketiga adalah “keuntungan” martabat yang disegani oleh masyarakat. Makna keempat adalah “keuntungan” kepuasan batin apabila pasien yang dirawatnya dapat sembuh.